Upaya Guru Pendidikan Pancasila dan Kewarganegaraan dalam Membentuk Sikap Bela Negara Pada Diri Siswa - Kartika Mawar Nurhaliza; Bambang Sutrisno (International Forum of Researchers and Lecturers, 2024)
Pancasila and citizenship education teachers play an important role in shaping students' national defense attitudes. Through a holistic and integrated learning approach, teachers are able to introduce the values ​​of Pancasila and citizenship as a whole. By teaching concepts such as mutual cooperation, justice, and diversity, teachers help students understand the importance of serving their country and society. In addition, through discussions, simulations and collaborative projects, teachers provide opportunities for students to internalize these values ​​in everyday life. Thus, Pancasila and citizenship education teachers play a role as the main pillar in forming the young generation who have a strong and responsible attitude of defending the country. The aim of this research is to provide awareness to Pancasila and citizenship education teachers to always form the young generation or students who have a high level of state defense attitude and can make students aware of the importance of a state defense attitude towards the country which is carried out by the role of Pancasila and citizenship education teachers. This research uses the Library Research method regarding the role of Pancasila and citizenship education teachers in forming an attitude of defending the country in students.